Pengaruh Komunikasi dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Esa Garda Pratama Jakarta Selatan - Syifa Azwa Fauziah; Mulyadi, Mulyadi (Yayasan Literasi Sains Indonesia, 2024)
This research investigates the influence of communication and work discipline on employee performance, both individually and collectively. The study employs quantitative methods, sampling 50 employees. It involves various tests: validity, reliability, classical assumption, descriptive analysis, correlation coefficient, coefficient of determination, and hypothesis testing. The multiple regression equation derived is Y = 6.679 + 0.469 X1 + 0.357 X2 + e. The communication variable's regression coefficient is 6.679, indicating that if communication (X1) and work discipline (X2) remain unchanged, the employee performance (Y) is 6.679. The statistical t-test shows a significant positive impact of communication on employee performance, with tcount at 5.972 > ttabel 2.011 and significance at 0.000 < 0.05, leading to acceptance of Ha and rejection of Ho. Thus, communication positively influences employee performance. Similarly, work discipline also shows a significant positive impact, with tcount at 5.426 > ttable 2.007 and significance at 0.000 < 0.05, confirming Ha and rejecting Ho. This indicates a significant positive effect of work discipline on employee performance. The statistical F-test confirms that the simultaneous effect of communication and work discipline on employee performance is significant, with F value at 22.894 > F table 3.200 and significance at 0.000 < 0.05. Therefore, the hypothesis that communication and work discipline jointly influence employee performance is supported. The study confirms both communication and work discipline are crucial for enhancing employee performance, emphasizing the importance of maintaining effective communication and high work discipline in organizational settings.